Breeding den selection by Arctic foxes (Vulpes lagopus) in southern Yamal Peninsula, Russia - Hofhuis, Stijn; Ehrich, Dorothee; Sokolova, Natalia A.; van Hooft, Pim; Sokolov, Aleksandr A. (Polar Biology, 2021)
Selecting the right location for a den during the breeding season is a type of habitat selection in the Arctic fox (Vulpes lagopus) that is likely to affect its reproductive success. A den’s suitability likely depends on its ability to provide shelter, as well as its proximity to prey resources. Depending on the different relative risks that Arctic foxes may face across their broad circumpolar range, Arctic foxes may place different emphases on selection for shelter and prey resources in different ecosystems. Understanding the different requirements for reproduction under different ecological conditions is highly relevant to conservation efforts in areas where Arctic foxes are threatened by rapid environmental changes. Here, we investigated the relative selection for shelter and prey resources in southern Yamal Peninsula (Russia) using data from 45 dens collected over a 13-year period. Arctic foxes preferred to breed in dens with more den entrances; an indicator of shelter quality. Arctic foxes also preferred dens surrounded by more prey resources (quantified by the amount of river valley habitat), but this result was less conclusive. These results complement the findings reported from other study areas, illustrating that Arctic foxes in ecosystems with diverse predator communities may put emphasis on selection for shelter quality. In less productive ecosystems, Arctic foxes may rather put emphasis on selection for prey resources. As tundra ecosystems become more productive and generalist predators move north, the reproductive requirements and habitat selection of Arctic foxes may change accordingly, depending on the species’ ability to adapt.